Investigating the Role of Technology in Language Education (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article gives information about how important the role of technology in learning languages and how to provide easy and effective way of teaching students and pupils. It is necessary to get acquainted with the general understanding of technology. Technology is one of the most important factors of progress in the course of training and training of schools and universities, especially for learning the language. This can help the teacher to present the best lesson for students. The technology is very necessary for education, because too many things that teachers can do such as a game, how to play any languages or songs, film and even theater. At the moment, there are now many research, they are schools, in some countries there are no technologies that are not used in their classes, except for private schools.